(NhOROWAQ LITERATURA(B.s (NU^EBNOE POSOBIE(B.s - (Ni(B.(NuSOWA(B.s ((NmOSKWAs (NmUZYKAs, 1988)
(Nu^EBNOE POSOBIE OHWATYWA@]EE WS@ PROGRAMMU KURSA HOROWOJ LITERATURY W MUZYKALXNOM U^ILI]E(B.s
Keywords: (NISTORIQs